(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Banking is no longer a business restricted to borrowing and lending of funds. Recent years have seen Indian commercial banks – both in the public sector and private sector diversify into new areas to widen their business horizons. As banks started offering diversified services ranging from insurance to mutual funds, from stock-broking to housing finance, from merchant banking to portfolio management under one ‘umbrella-brand’, they gradually metamorphosed from being business organisations having prime focus on money transactions to a business related to information on financial transactions. Thus, with this transition, banks gradually moved towards becoming ‘Universal banks’.Risk Management is the application of proactive strategy to plan, lead, organize, and control the wide variety of risks that are rushed into the fabric of an organization’s daily and long-term functioning. Like it or not, risk has a say in the achievement of our goals and in the overall success of an organization. Present paper is to make an attempt to identify the risks faced by the banking industry and the process of risk management. This paper also examined the different techniques adopted by banking industry for risk management. To achieve the objectives of the study data has been collected from secondary sources i.e., from Books, journals and online publications, identified various risks faced by the banks, developed the process of risk management and analyzed different risk management techniques. Finally it can be concluded that the banks should take risk more consciously, anticipates adverse changes and hedges accordingly, it becomes a source of competitive advantage, and efficient management of the banking industry. The regulatory framework would need to be strengthened so as to cover all aspects of Universal Banking either under control of one regulator or a coordinating mechanism would have to be developed among different regulators like the Reserve Bank of India, SEBI, Insurance Regulatory, Authority etc. The regulators will have to frame sound mechanism to protect the interests of all concerned including the customer, the Universal Banking Institution and the financial system of the country.